Method for regulating distribution of nanocrystalline region of nanocrystalline inclusion configuration aluminum matrix composite and application
Patent Information
- Application Number
- CN202410392609.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-02
AI Technical Summary
[0003]目前粗细晶构型复合材料中存在以下问题:(1)复合材料中粗晶区与细晶区强度差异大,不合理的比例设计下变形过程中两种尺度晶区因明显的变形差异产生界面开裂;(2)缺少粗细晶构型复合材料中细晶区分布以及形态对力学性能影响的研究;(3)缺少对细晶区形态调控,优化构型复合材料强化效果的相关制备研究
[0026](1)本发明通过利用不同含量的过程控制剂对细晶区的尺寸、分布以及形态进行调控,得到不同构型特征复合材料,可做到对复合材料力学性能有益的有利构型的快速筛选。
Smart Images

Figure CN118326189B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal matrix composite material preparation, specifically relating to a method and application for controlling the distribution of nanocrystalline regions in a nanocrystalline inclusion-structured aluminum matrix composite material. Background Technology
[0002] The inversion of strength and plasticity is a common challenge in traditional homogeneous metal matrix composites. In recent years, non-homogeneous metal matrix composites have shown breakthrough potential in addressing the strength-plasticity balance problem due to their unique structural design. Coarse-grained and fine-grained composites can generate back stress reinforcement during deformation by coordinating deformation, while the coarse grains improve plasticity and blunt crack tips, resulting in good strength-plasticity balance. However, current research has not delved into the matching and distribution of coarse-grained and fine-grained structures in these composites, and the strengthening effect brought by the coarse-grained and fine-grained configuration has not been fully realized. Further research is needed to explore how to control the characteristics of the coarse-grained and fine-grained configuration to maximize the strengthening effect.
[0003] The following problems exist in coarse and fine crystal composites: (1) There is a large difference in strength between the coarse and fine crystal regions in the composite material. Under unreasonable proportional design, the two crystal regions of different scales will crack at the interface due to obvious deformation differences during deformation. (2) There is a lack of research on the distribution and morphology of the fine crystal region in coarse and fine crystal composites and their influence on mechanical properties. (3) There is a lack of relevant preparation research on the control of the morphology of the fine crystal region and optimization of the strengthening effect of the composite material. Summary of the Invention
[0004] To overcome the above-mentioned technical problems, the present invention provides a method and application for controlling the distribution of nanocrystalline regions in aluminum matrix composites with nanocrystalline inclusion configurations.
[0005] The technical solution of the present invention is as follows:
[0006] One objective of this invention is to provide a method for controlling the distribution of nanocrystalline regions in aluminum matrix composites with nanocrystalline inclusions, which is carried out according to the following steps:
[0007] S1: Hard nanoparticles and aluminum powder are mixed at low speed until uniform, and then subjected to high-energy ball milling. During the ball milling process, a process control agent is added and its addition amount is controlled to obtain a nanocrystalline aggregate.
[0008] S2: Flexible nano-carbon material and aluminum powder are mixed at low speed until uniform and then ball-milled at medium energy. A process control agent is added during the ball milling process and its addition amount is controlled to obtain micro-nano crystal aggregates.
[0009] S3: Nanocrystalline aggregates and micro / nanocrystalline aggregates are ball-milled with aluminum powder at a certain volume ratio. A process control agent is added during the ball milling process and its addition amount is controlled to regulate the distribution of nanocrystalline regions in the composite material. Subsequently, spark plasma sintering and hot extrusion are performed to obtain a nanocrystalline inclusion aluminum matrix composite material.
[0010] Further specifying, the process control agent mentioned in S1-3 is one of stearic acid, hexane, oxalic acid, methanol, ethanol, alumina, and aluminum nitride.
[0011] Further specified, the speed of low-speed mixing in S1 is 100-250 rpm, and the time is 1-8 hours.
[0012] Further specified, the high-energy ball mill in S1 has a rotation speed of 300-800 rpm and a time of 5-15 h.
[0013] Further specified, the amount of process control agent added in S1 is 0.5% to 2.5% of the total mass of the powder.
[0014] Further specifying, the hard nanoparticles in S1 are one of silicon carbide (SiC), silicon nitride (Si3N4), and aluminum oxide (Al2O3).
[0015] Further specified, the speed of low-speed mixing in S2 is 40-200 rpm, and the time is 3-20 h.
[0016] Further specifying, the rotation speed of the medium-energy ball mill in S2 is 250-300 rpm, and the time is 1-5 h.
[0017] Further specified, the amount of process control agent added in S2 is 0.5% to 1% of the total mass of the powder.
[0018] Further specifying, the flexible carbon nanomaterial in S2 is selected from one of graphene nanosheets, carbon nanotubes, carbon nanofibers, and carbon nanospheres.
[0019] Further specified, the rotation speed of the S3 low-speed ball mill is 150-450 rpm, and the time is 1-20 h.
[0020] Further specified, the amount of process control agent added in S3 is 0 to 0.5% of the total mass of the powder.
[0021] Further specifying, the volume percentages of nanocrystalline aggregates, micro-nanocrystalline aggregates, and aluminum powder in the nanocrystalline inclusion-structured aluminum matrix composite material of S3 are 30-60%, 20-40%, and 10-30%, respectively.
[0022] Further specifying, the content of hard nanoparticles in the S3 nanocrystalline intercalated aluminum matrix composite material is 1–10 vol.%, and the content of flexible nanocarbon materials is 0.5–3 vol.%.
[0023] The second objective of this invention is to provide an application of the above-mentioned method in the regulation of the distribution of nanocrystalline regions in nanocrystalline inclusion-structured metal matrix composites.
[0024] Further specified, the metal matrix is one or more of Al, Mg, Fe, Ti, and Cu.
[0025] The advantages of this invention compared to existing technologies are:
[0026] (1) This invention uses process control agents of different contents to regulate the size, distribution and morphology of fine-grained regions to obtain composite materials with different configuration characteristics, and can quickly screen the advantageous configurations that are beneficial to the mechanical properties of composite materials.
[0027] (2) This invention optimizes the distribution of nanocrystalline regions and the optimal combination of each crystal region by controlling the morphological distribution of fine-grained regions and combining the proportion design of each crystal region. This results in a range of nanocrystalline region size and morphological distribution that is conducive to improving material performance, thereby achieving significant optimization of mechanical properties and providing a positive reference for performance improvement in the field of composite materials.
[0028] (3) This invention achieves performance optimization of configuration composite materials by controlling the content of process control agent. It is low in cost, simple in process, and controllable in process, suitable for industrial production, meets the customized needs of composite materials with diverse performance, and has broad industrial prospects. Attached Figure Description
[0029] Figure 1 This is the SEM morphology of Al-SiCnp ball-milled powder in Example 4 of the present invention;
[0030] Figure 2 This is the SEM morphology of Al-SiCnp ball-milled powder in Example 6 of the present invention;
[0031] Figure 3 This is the SEM morphology of Al-SiCnp ball-milled powder in Comparative Example 1 of the present invention;
[0032] Figure 4 This describes the EBSD grain morphology of the extruded sample in Example 5 of the present invention.
[0033] Figure 5 This is the grain morphology of the extruded EBSD sample in Comparative Example 1 of the present invention;
[0034] Figure 6 This refers to the statistical analysis of the fine-grained region size in the extruded samples of Examples 4-7 and Comparative Example 1 of the present invention;
[0035] Figure 7 This is a metallographic morphology image of the extruded sample in Example 1 of the present invention;
[0036] Figure 8 These are the tensile mechanical property curves of the extruded samples in Examples 1-7 and Comparative Example 1 of the present invention. Detailed Implementation
[0037] This invention provides a method for controlling the distribution of nanocrystalline regions in aluminum matrix composites with nanocrystalline inclusions, specifically comprising the following steps:
[0038] (1) Hard nanoparticles and aluminum powder are mixed at low speed until uniform and then subjected to high-energy ball milling. During the ball milling process, a process control agent is added and its addition amount is controlled to obtain a nanocrystalline aggregate.
[0039] (2) After mixing the flexible nano-carbon material with aluminum powder at low speed until uniform, the mixture is ball-milled at medium energy. During the ball milling process, a process control agent is added and its addition amount is controlled to obtain a micro-nano crystal aggregate.
[0040] (3) The nanocrystalline aggregates and micro-nanocrystalline aggregates are ball-milled with aluminum powder at a certain volume ratio. During the ball milling process, a process control agent is added and its addition amount is controlled to complete the regulation of the distribution of nanocrystalline regions in the composite material.
[0041] (4) Perform discharge plasma sintering and hot extrusion to obtain a nanocrystalline mixed aluminum matrix composite material.
[0042] In the above specific embodiments, the hard nanoparticles in step (1) are one of silicon carbide (SiC), silicon nitride (Si3N4), and aluminum oxide (Al2O3), with a size of 20-80 nm. The low-speed mixing speed is 100-250 rpm, and the time is 1-8 h. The high-energy ball milling speed is 300-800 rpm, and the time is 5-15 h. The process control agent is one of stearic acid, hexane, oxalic acid, methanol, ethanol, aluminum oxide, and aluminum nitride, and its addition amount is 0.5-2.5% of the total mass of the powder, more preferably 1-2.5%.
[0043] In the above specific embodiments, the flexible nano-carbon material mentioned in step (2) is selected from graphene nanosheets, carbon nanotubes, carbon nanofibers, and carbon nanospheres, and has at least one dimension smaller than 100 nm. The low-speed mixing speed is 40-200 rpm, and the time is 3-20 h. The medium-energy ball milling speed is 250-300 rpm, and the time is 1-5 h. The process control agent is one of stearic acid, hexane, oxalic acid, methanol, ethanol, alumina, and aluminum nitride, and its addition amount is 0.5-1% of the total mass of the powder.
[0044] In the above specific embodiments, the volume percentages of the nanocrystalline aggregates, micro-nanocrystalline aggregates, and aluminum powder in the nanocrystalline mixed-structure aluminum matrix composite material in step (3) are 30-60%, 20-40%, and 10-30%, respectively. The content of hard nanoparticles in the nanocrystalline mixed-structure aluminum matrix composite material is 1-10 vol.%, and the content of flexible nano-carbon materials is 0.5-3 vol.%. The low-speed ball milling speed is 150-450 rpm, and the time is 1-20 h. The process control agent is one of stearic acid, hexane, oxalic acid, methanol, ethanol, alumina, and aluminum nitride, and its addition amount is 0-0.5% of the total mass of the powder.
[0045] In the above specific embodiments, the grinding balls used in the ball mill in steps (1), (2) and (3) are all stainless steel balls, and the ball-to-material ratio is (5-20):1.
[0046] In the above specific embodiment, the sintering temperature in step (4) is 400-550℃, the pressure is 40-100MPa, and the time is 5-15min. The hot extrusion temperature is 300-500℃, and the hot extrusion ratio is (6-36):1.
[0047] A further preferred embodiment is that the volume percentage of the nanocrystalline aggregate in the nanocrystalline inclusion-structured aluminum matrix composite material is 35-50%.
[0048] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0049] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.
[0050] In the following embodiments, the grinding balls used in the ball mills are all stainless steel balls, and the ball-to-material ratio is 15:1.
[0051] Example 1: The method for controlling the mixed crystal ratio of the multi-stage aluminum-based composite material in this example is carried out according to the following steps:
[0052] (1) Mix nano-silicon carbide particles SiCnp (particle size 20-80nm) with aluminum powder (particle size 5-25μm) at 200rpm for 5h until uniform, and then ball mill at 300rpm for 10h. During the ball milling process, add stearic acid accounting for 1.5% of the total mass of the powder to obtain Al-SiCnp nanocrystal aggregates.
[0053] (2) Graphene nanosheets GNS (thickness of 5-10 nm, average diameter of 1.6 μm) and aluminum powder (particle size of 5-25 μm) were mixed at 200 rpm for 5 h until uniform, and then ball-milled at 300 rpm for 2 h at medium energy. During the ball milling process, 0.5% of stearic acid was added to obtain Al-GNS micro-nano crystal aggregates.
[0054] (3) Al-SiCnp nanocrystal aggregates, Al-GNS micro-nanocrystal aggregates and remaining aluminum powder were ball-milled at 200 rpm for 5 h in a volume ratio of 50:40:10 to obtain nanocrystal mixed-structure composite powder, wherein the volume fraction of aluminum powder was 97 vol%, the volume fraction of graphene nanosheets GNS was 1.5 vol%, and the volume fraction of nano-silicon carbide particles SiCnp was 1.5 vol%.
[0055] (4) The nanocrystalline mixed-structure composite powder is placed in a mold for vacuum discharge plasma sintering (SPS) at a temperature of 530°C and a pressure of 50 MPa. The temperature and pressure are maintained for 5 minutes. Then it is loaded into an extrusion mold for preheating and hot extrusion at 490°C with an extrusion ratio of 25:1. Finally, the nanocrystalline mixed-structure aluminum matrix composite material, abbreviated as NG50-1.5PCA, is obtained.
[0056] Example 2
[0057] The method for controlling the mixed crystal ratio of the multi-level mixed aluminum matrix composite material in this embodiment is the same as that in Embodiment 1, except that: in step (3), the volume ratio of Al-SiCnp nanocrystal aggregate, Al-GNS micro / nanocrystal aggregate and the remaining aluminum powder is 40:40:20, and the proportion of Al-SiCnp nanocrystal region in the obtained product is 40 vol.%, the proportion of Al-GNS micro / nanocrystal region is 40 vol.%, and the proportion of pure matrix microcrystal region is 20 vol.%. The obtained composite material is referred to as NG40-1.5PCA.
[0058] Example 3
[0059] The method for preparing the multi-stage mixed aluminum matrix composite material in this embodiment is controllable in terms of the mixed crystal ratio. The specific steps are the same as in Embodiment 2, except that in step (1), the stearic acid content is 1.0 wt%. The resulting composite material is referred to as NG40-1.0PCA.
[0060] Example 4
[0061] The method for preparing the multi-level mixed aluminum matrix composite material with controllable mixed crystal ratio in this embodiment is the same as that in Example 1, except that: in step (1), the stearic acid content is 1.0 wt%; in step (3), the volume ratio of Al-SiCnp nanocrystal aggregate, Al-GNS micro / nanocrystal aggregate and remaining aluminum powder is 35:35:30; and the proportion of Al-SiCnp nanocrystal region in the obtained product is 35 vol.%, the proportion of Al-GNS micro / nanocrystal region is 35 vol.%, and the proportion of pure matrix microcrystal region is 30 vol.%. The obtained composite material is abbreviated as NG35-1.0PCA.
[0062] Example 5
[0063] The method for preparing the multi-stage mixed aluminum-based composite material in this embodiment is controllable in terms of the mixed crystal ratio. The specific steps are the same as in Example 4, except that in step (1), the stearic acid content is 1.5 wt%. The resulting composite material is referred to as NG35-1.5PCA.
[0064] Example 6
[0065] The method for preparing the multi-stage mixed aluminum matrix composite material in this embodiment is controllable in terms of the mixed crystal ratio. The specific steps are the same as in Example 4, except that in step (1), the stearic acid content is 2.0 wt%. The resulting composite material is referred to as NG35-2.0PCA.
[0066] Example 7
[0067] The method for preparing the multi-stage mixed aluminum-based composite material in this embodiment is controllable in terms of the mixed crystal ratio. The specific steps are the same as in Example 4, except that in step (1), the stearic acid content is 2.5 wt%. The resulting composite material is referred to as NG35-2.5PCA.
[0068] Comparative Example 1:
[0069] The method for preparing the multi-stage mixed aluminum matrix composite material of this comparative example with controllable mixed crystal ratio is the same as that in Example 4, except that in step (1), the stearic acid content is 3.0 wt%. The resulting composite material is referred to as NG35-3.0PCA.
[0070] Figure 1 , Figure 2 , Figure 3The figures show the powder morphology after high-energy ball milling of aluminum powder and SiCnp in Examples 4, 6, and Comparative Example 1, respectively. The stearic acid content added to the three samples at this stage was 1.0, 2.0, and 3.0 wt%, respectively. A comparison of the three figures clearly shows that the size of the cold-welded aluminum particles decreases significantly with increasing stearic acid content. When the stearic acid content is 1.0 wt%, the ball-milled aluminum is cold-welded into large particles with a radial size reaching hundreds of micrometers. When the stearic acid content is 2.0 wt%, the radial size and thickness of the ball-milled aluminum powder decrease significantly, transforming into flake-like aluminum powder. When the stearic acid content reaches 3.0 wt%, the aluminum powder size decreases significantly, with most radial sizes within 10 μm. The size statistics of Al-SiCnp ball milled powder obtained by adding 1.0-3.0 wt.% stearic acid to Al and SiCnp in ball milling with a nanocrystal content of 35% in Examples 4-7 and Comparative Example 1 are shown in Table 1. It can be seen that with the increase of stearic acid content, the size of aluminum powder obtained by ball milling is significantly reduced in both flake diameter and thickness.
[0071] Table 1. Sizes of Al-SiCnp ball-milled powders
[0072]
[0073] Figure 4 and Figure 5 The EBSD grain morphology of the extruded composite materials obtained in Example 5 and Comparative Example 1 are shown, respectively. Figure 4 It can be seen that the nanocrystalline region of the composite material is deformed and elongated along the extrusion direction, exhibiting a streamlined distribution. The nanocrystalline particles are surrounded by coarse grains, demonstrating obvious nanocrystalline inclusion characteristics. Figure 5 It can be seen that when 3.0 wt.% stearic acid is added during the ball milling of Al powder and SiCnp, the size of the aluminum powder after ball milling is reduced to the minimum, the composite material configuration characteristics disappear, and no obvious nanocrystalline region can be distinguished in the EBSD results. As the stearic acid content increases, the composite material configuration characteristics disappear, and the obvious nanocrystalline inclusion configuration is transformed into a uniform structure.
[0074] Figure 6 Table 2 summarizes the specific data for the size statistics of the nanocrystalline regions in Examples 4-7 and Comparative Example 1. As the stearic acid content increases in step 1, the length and width of the nanocrystalline regions in the composite material gradually decrease after hot extrusion. Statistical analysis of the aspect ratio of the nanocrystalline regions shows that in Comparative Example 1, the aspect ratio of the nanocrystalline regions reaches its maximum and the streamline characteristics are most obvious when the stearic acid content is 1.5 wt.%.
[0075] Table 2. Size of the fine-grained region in the extruded samples.
[0076]
[0077]
[0078] Figure 7 The image shows the metallographic morphology of the extruded composite material with a nanocrystal content of 50 vol.% and 1.5 wt.% stearic acid added during the ball milling of Al powder and SiCnp, as described in Example 1. The darker areas are Al-SiCnp nanocrystal regions, which are regularly arranged and distributed in a streamlined manner, alternating with the lighter-colored coarse-grained regions. The aspect ratio of the nanocrystal regions exceeds 100.
[0079] Figure 8 The tensile mechanical property curves of the extruded samples in Examples 1-7 and Comparative Example 1 are shown in Table 3. The specific data are summarized in Table 3. As can be seen from the figure, compared to the composite material of Comparative Example 1 with the highest stearic acid content (3.0 wt.%) and a more uniform structure, the composite materials with nanocrystalline inclusions in the other groups exhibit higher tensile strength. In the composite material with a nanocrystalline content of 35 vol.%, the nanocrystalline region contains 1.5 wt.% stearic acid, meaning the composite material in Example 5 achieves the optimal comprehensive mechanical properties. Based on previous data analysis, the aspect ratio of the nanocrystalline region in this composite material reaches its highest level (21.15). Based on the addition of 1.5 wt.% stearic acid to the nanocrystalline region, the strength and plasticity of the composite material are simultaneously improved when the nanocrystalline content is increased to 40% and 50%. In Example 1, the composite material performance is optimal when the nanocrystalline content is 50 vol.%, with a tensile strength of 294 MPa and a simultaneously improved elongation at a good level (10.2%).
[0080] Table 3 Mechanical properties of the extruded samples
[0081]
[0082]
[0083] The above description is merely a preferred embodiment of the present invention. These specific embodiments are different implementations based on the overall concept of the present invention, and the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for controlling the distribution of nanocrystalline regions in a nanocrystalline-intercalated aluminum matrix composite material, characterized in that, Follow these steps: S1: Hard nanoparticles are mixed with aluminum powder at low speed until homogeneous, and then subjected to high-energy ball milling. During the ball milling process, a process control agent is added and its addition amount is controlled to obtain nanocrystalline aggregates; the amount of process control agent added is 0.5~2.5% of the total mass of powder. S2: Flexible nano-carbon material and aluminum powder are mixed at low speed until homogeneous, and then ball-milled at medium energy. A process control agent is added during the ball milling process, and the amount added is controlled to obtain micro-nano crystal aggregates; the amount of process control agent added is 0.5~1% of the total mass of powder. S3: Nanocrystalline aggregates and micro / nanocrystalline aggregates are ball-milled with aluminum powder at a volume ratio of 30-60:20-40:10-30. A process control agent is added during the ball milling process, and its addition amount is controlled to regulate the distribution of nanocrystalline regions in the composite material. Subsequently, spark plasma sintering and hot extrusion are performed to obtain a nanocrystalline mixed-structure aluminum matrix composite material. The amount of process control agent added is 0-0.5% of the total mass of powder and is not zero. The content of hard nanoparticles in the nanocrystalline mixed-structure aluminum matrix composite material is 1-10 vol.%, and the content of flexible nano-carbon material is 0.5-3 vol.%.
2. The method according to claim 1, characterized in that, The process control agent mentioned in S1-3 is one of stearic acid, hexane, oxalic acid, methanol, and ethanol.
3. The method according to claim 1, characterized in that, The low-speed mixing in S1 is performed at a speed of 100~250 rpm for 1~8 h, while the high-energy ball milling is performed at a speed of 300~800 rpm for 5~15 h. The hard nanoparticles are one of silicon carbide (SiC), silicon nitride (Si3N4), and aluminum oxide (Al2O3).
4. The method according to claim 1, characterized in that, The S2 low-speed mixing speed is 40~200 rpm and the time is 3~20h. The medium-energy ball milling speed is 250~300 rpm and the time is 1~5h. The flexible nano-carbon material is selected from one of graphene nanosheets, carbon nanotubes, carbon nanofibers, and nano-carbon spheres.
5. The method according to claim 1, characterized in that, The rotation speed of the S3 low-speed ball mill is 150~450 rpm, and the time is 1~20h.
6. The application of the control method according to any one of claims 1-5 in the control of the distribution of nanocrystalline regions in nanocrystalline inclusion-structured aluminum matrix composites.
Citation Information
Patent Citations
Preparation method of aluminum-based composite material
CN113186418A
Preparation method of graphene and silicon carbide hybrid reinforced aluminum-based composite material
CN114951664A